Examining the Post-High School Effects of a Primary Prevention Program on Exposure to Bullying and Sexual Violence among Emerging Adults. Issue 9 (May 2022) - Williford, Anne; Yoder, Jamie; Sharp, Julia; Tunstall, Ashley; Espelage, Dorothy L; Ortega, Lilyana; Fulginiti, Anthony
Emerging adulthood (EA) is a time of self-exploration as new opportunities for independence and autonomy arise. Yet, for some youth, this may also contribute to instability, uncertainty, and anxiety. Consequently, evidence suggests that rates of exposure to various forms of violence increase in EA. This study examined changes in experiences of bullying and sexual violence (SV) victimization among a sample of post-high school emerging adults who were exposed to a primary prevention program, Sources of Strength ( Sources ). We also examined whether Sources skills (e.g., healthy coping and help-seeking) buffer against these experiences. Participants were 102 emerging adults (73.5% identifying as female, 36.3% as Latinx, and 22.6% as LGBQ), who completed surveys at three time points: 1 month prior to graduation and at 6- and 12-months post-graduation. Results suggest that as youth transition into emerging adulthood, experiences of bullying victimization were relatively low and slightly decreased whereas experiences of SV were also relatively low, but stable over time. Notably, bullying victimization was lower when female-identifying participants, relative to males, had higher levels of healthy coping. In addition, SV victimization for participants identifying as non-white was higher at lower levels of coping than those identifying as white; however, at higher levels of coping, non-white participants reported lower rates of SV victimization, while rates were relatively stable for white participants at high and low levels of coping. These findings provide some support for the Sources program model where engaging in healthy coping may protect young women from bullying exposure and buffer against SV victimization for racial and ethnic minoritized young adults. Implications for violence prevention are discussed.